2022
DOI: 10.1002/fsh.10823
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Angler Contributions to Fisheries Management Are Varied and Valuable: Case Studies from South Florida

Abstract: Recreational fisheries are complex social–ecological systems that are influenced by a variety of increasing stressors. In Florida (USA), recreational fishing is a US$9.2 billion industry and a vital aspect of the state's culture. However, many targeted species remain unregulated and understudied, which hinders identifying population declines or important ecological interactions. The complex nature of recreational fishing means traditional data collection and analysis methods for assessing stock status and tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In our study, we solicited the aid of experienced recreational fishing guides to fill in knowledge gaps about the Crevalle Jack fishery and to help inform model priors. Studies have shown that fishing guides are ideal research partners, as they have substantial on‐the‐water experience and a vested interest in fisheries conservation (Kroloff et al 2019; Adkins 2020; Gervasi et al 2022a). To ensure continued trust and collaboration, fishing guides were informed of the results of this study and its potential management applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we solicited the aid of experienced recreational fishing guides to fill in knowledge gaps about the Crevalle Jack fishery and to help inform model priors. Studies have shown that fishing guides are ideal research partners, as they have substantial on‐the‐water experience and a vested interest in fisheries conservation (Kroloff et al 2019; Adkins 2020; Gervasi et al 2022a). To ensure continued trust and collaboration, fishing guides were informed of the results of this study and its potential management applications.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure continued trust and collaboration, fishing guides were informed of the results of this study and its potential management applications. As demonstrated by Gervasi et al (2022a), it is important to involve anglers throughout the scientific research process and beyond to maintain trusted partnerships. For cases in which there is general distrust of science and management by key stakeholders, efforts to build trust and maintain relationships are vital to conducting LEK research and fisheries co‐management (Thornton and Scheer 2012; Rubert‐Nason et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority visited the Bay at least once per year. The frequency and popularity of certain activities, including beach visits and recreational angling were not surprising—beach tourism and recreational angling are both extremely popular statewide and considered important local industries [ 59 , 60 ]. Fishing for food was the second most common activity amongst participants.…”
Section: Discussionmentioning
confidence: 99%